Diagnosis of blue and sustainable entrepreneurship in university education in Spain: a case study - Poza Vílchez, Fátima; Arjona Romero, Juan José; Martín-Jaime, Juan Jesús (Journal of Teacher Education for Sustainability, 2023)
University education, in terms of its social and environmental responsibility, plays an important role in promoting local and global sustainability from its fundamental corporate principles: “Mission, Vision and Values”. Four dimensions associated with fourteen values related to blue and sustainable entrepreneurship were considered in this study: “Entrepreneurship values”, “Personal values”, “Social values” and “Environmental values” (the variables that are the object of this diagnostic study), which enabled the internal correlations that occurred between them to be seen, according to their level of presence in degree qualification syllabi at public universities in the region of Andalusia (Spain). The main conclusion we have found is the importance of prioritizing the “Personal” dimension in university education as an exogenous variable that conditions the social and entrepreneurship values, which also has a direct effect on the values related to the “Environmental” dimension, with the purpose of achieving a balanced and significant presence of values related to blue and sustainable entrepreneurship.
Keywords: Enseñanza superior; Blue entrepreneurship; Higher education; Pro-sustainable values; Sustainable teacher education